Justification of Plants Water Demand in Conditions of Drip Irrigation - Yeghiazaryan, G․ M․; Navoyan, G․ R․; Tamoyan, S. J. (ՀԱԱՀ հիմնադրամ)
In the current work, a comprehensive methodology for the soil and climatic conditions of the Republic of Armenia has been developed to justify the water requirement/demand of plants in the case of drip irrigation. The proposed methodology enables to calculate the values of the individual components of the drip irrigation regime, and in practical terms, it was used to determine the water requirement of perennial plantations in the soil and climatic conditions of the Armavir and Kotayk marzes. Based on the obtained results, the crops drip irrigation norms/rates were mapped in the GIS environment. They can serve as a background for practical planning and justification of the drip irrigation water demand for various crops and contribute to the development of introduction rates of water-saving technologies in this field.
Keywords: Agricultural Engineering; Irrigation